Comprehensive study of angiogenic factors in women with endometriosis compared to women without endometriosis. (September 2016) - Yerlikaya, Gülen; Balendran, Sukirthini; Pröstling, Katharina; Reischer, Theresa; Birner, Peter; Wenzl, Rene; Kuessel, Lorenz; Streubel, Berthold; Husslein, Heinrich
Abstract: Objective: Endometriosis is a benign gynaecological disease, affecting women during their reproductive years. Angiogenesis represents a crucial step in the pathogenesis of endometriosis, because endometriotic lesions require neovascularization. In this study several angiogenesis-related genes have been studied in the context of endometriosis. Some of the analyzed angiogenic factors as well as their interactions were studied the first time regarding a possible association with endometriosis. Study design: This case-control study consisted of 205 biopsies of 114 patients comprising 61 endometriosis patients and 53 control patients. Among them in 29 cases paired samples were obtained. VEGFA, VEGFR2, HIF1A, HGF, NRP1, PDGFB, FGF18, TNFα, TGFB2, EPHB4, EPO and ANG mRNA expression was analyzed by qRT-PCR in ectopic tissue samples, in eutopic endometrium of women with and without endometriosis, and in unaffected peritoneum of women with and without endometriosis. Results: VEGFR2, HIF1A, HGF, PDGFB, NRP1 and EPHB4 are overexpressed in ectopic lesions compared to eutopic tissues. VEGFR2, HGF, PDGFB, NRP1, and EPHB4 showed highest mRNA levels in peritoneal implants, in contrast HIF1A showed the highest expression in ovarian endometriomas. Correlation analyses of angiogenic factors in ectopic lesions revealed the strongest associations between VEGFR2, PDGFB, and EPHB4 . We further showed a significant upregulation of VEGFR2, HIF1A and EPHB4 in eutopic endometrium of women with endometriosis compared to that of controls and a trend towards upregulation of HGF . Additionally, a significant downregulation for HIF1A, HGF and EPHB4 was observed in unaffected peritoneal tissues of women with endometriosis compared to controls. Conclusion: We identified new genes ( EPHB4 and NRP1 ) that may contribute to angiogenesis in endometriosis beside known factors ( VEGFA, VEGFR2, HIF1A, HGF, and PDGFB ). Correlation studies revealed the putative importance of EBHB4 in association with endometriosis. Our analyses support preliminary reports that angiogenic factors seem to be differently expressed in peritoneal implants, ovarian endometriomas and deep infiltrating endometriosis. Our observation that angiogenic factors are differently expressed in the unaffected peritoneum of women with endometriosis compared to women without endometriosis underlines the importance of the peritoneum in the establishment of endometriosis.